The construction of entrepreneurial practices in family businesses: A study in the cachaça industry - Borges, Alex Fernando; Volta, Carolina Lescura de Carvalho Castro; Brito, Mozar José de; Lima, Juvêncio Braga de (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
The purpose of this paper is to comprehend the construction of entrepreneurial practices in family businesses. In order to do so, we studied four family businesses from the cachaça industry through a qualitative multicase study. We observed that entrepreneurial practices of organization creation, of opportunities’ identification and exploration, of production and commercialization, and of innovation, contributed alltogheter for these businesses’ evolution, competitivity and survival. Therefore, we consider the approach of entrepreneurship through entrepreneurial practices may constitute an alternative for the development of the field, contributing to a more comprehensive analysis of entrepreneurial phenomena in general, and of family businesses in particular.